Can Political Empowerment Help Economic Empowerment? Women Leaders and Female Labor Force Participation in India - Ghani, Ejaz; Mani, Anandi; O'Connell, Stephen D. (World Bank, Washington, DC, 2014)
This study examines whether political empowerment of women affects their economic participation. In the context of mandated political representation reform for women in India, the study finds that the length of exposure to women politicians affects overall female labor force participation. These effects seem to arise through direct and indirect channels: political representation of women directly affects hours of work assigned to women under the recent national public works program, the Mahatma Gandhi National Rural Employment Guarantee Scheme. In addition, the level of access to public goods, as influenced by exposure to women leaders over time, increases the likelihood of women being engaged in the labor force. The findings suggest that women's participation in politics could be a useful policy tool to increase both the supply of and the demand for labor market opportunities for women, potentially helping to stem India's declining female labor force participation rate.